A TiO2 / SiO x Bulk bicontinuous structure electrode material and its preparation method and application
By adopting the TiO2/SiOx body-phase dual continuous structure in the negative electrode material of lithium-ion batteries, the problem of poor electrochemical performance of existing materials is solved, and the improvement of high energy density, long cycle life and fast charging performance is achieved.
Patent Information
- Application Number
- CN202210933937.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-08-04
AI Technical Summary
The electrochemical performance of existing lithium-ion battery anode materials is poor, making it difficult to meet the needs of high energy density, long cycle life and fast charging performance.
Using TiO2/SiOx bulk-phase bicontinuous structure electrode material, a bicontinuous structure with less than 10nm is formed by combining the bridged TiO2 nanoparticles and SiOx nanoparticles network structure, reducing volume expansion and improving electrochemical performance.
The lithium-ion battery negative electrode material that achieves high capacity, long cycle life and fast charging performance improves energy density and shows excellent stability and fast charging performance.
Smart Images

Figure CN115332524B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nanomaterials and electrochemical technology, and in particular to a TiO2 / SiO x Bulk bicontinuous structure electrode material and its preparation method and application. Background Art
[0002] As one of the representatives of clean energy storage systems, lithium-ion batteries have the advantages of high energy density and high power density, and are widely used in automotive power batteries, large-scale energy storage, and portable electronic devices. However, the current commercial graphite anode has a low specific capacity (372mAh g -1 ), poor safety (low lithiation potential), and it is difficult to meet the growing energy density requirements. And with the further expansion of energy demand, the shortage of lithium resources will seriously restrict its application and development, which also puts forward higher requirements for the full utilization of limited lithium resources: further improve the capacity, rate performance and cycle life of electrode materials under existing conditions.
[0003] Titanium dioxide (TiO2) is considered to be a stable and safe anode material for lithium-ion batteries due to its high mechanical stability and slight volume change upon lithiation (≈4%). In addition, the highly conductive and ion-conductive TiO2 lithiation product (Li y TiO2, 0<y<1, can promote the kinetic process of lithium ionization, thus achieving better fast charging performance. x ) has the advantages of high capacity and high energy density, but its large lithiation volume expansion rate (≈200%) limits its application.
[0004] Therefore, how to combine TiO2 and SiO x Combining the advantages of both and compensating for the other disadvantages to construct a lithium-ion electrode material with high capacity, fast charging performance and long cycle has become a rational and efficient solution for lithium-ion battery negative electrode materials. Summary of the invention
[0005] In view of this, the present invention provides a TiO2 / SiO x Bulk phase dual continuous structure electrode material and preparation method and application thereof are used to solve the problem of poor electrochemical performance of existing lithium ion battery negative electrode materials.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A TiO2 / SiO xBulk phase double continuous structure electrode material, comprising a first continuous structure and a second continuous structure plugged into the first continuous structure, the first continuous structure is a bridged TiO2 nanoparticle, the second continuous structure is a SiO x Nanoparticle network structure, wherein 0.5<x<2, the SiO x The particle size of the nanoparticles is smaller than that of the TiO2 nanoparticles, and the particle size of the TiO2 nanoparticles is not greater than 10 nm.
[0008] According to the above scheme, the particle size of the TiO2 nanoparticles is in the range of 2nm to 10nm.
[0009] According to the above scheme, the SiO x The particle size of nanoparticles ranges from 1 nm to 5 nm.
[0010] According to the above scheme, the TiO2 / SiO x The bulk structure of the bulk bicontinuous structure electrode material is a sphere, and the diameter of the sphere is in the range of 0.1um to 5um.
[0011] Based on the above scheme, the second object of the present invention is to provide a TiO2 / SiO x A method for preparing a bulk bicontinuous structure electrode material comprises the following steps:
[0012] The Ti3SiC2 MAX phase ceramic powder is ball-milled, and the ball-milled product is sintered in air to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
[0013] According to the above scheme, the ball milling conditions include: rotation speed 100-600rpm, ball milling time 0.5-48h.
[0014] According to the above scheme, the sintering conditions include: sintering temperature 500-1200°C, heating time 0.5-6h.
[0015] According to the above scheme, the purity of the Ti3SiC2 MAX phase ceramic powder is not less than 90%.
[0016] Based on the above scheme, the third object of the present invention is to provide a TiO2 / SiO x Application of bulk bicontinuous structure electrode materials as negative electrode active materials for lithium-ion batteries.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] (1) TiO2 / SiO xBulk bicontinuous structure electrode material, bridged TiO2 nanoparticles as active material and structurally stable skeleton, continuous SiO x In the bulk phase, continuous TiO2 nanoparticles exist in a bicontinuous "intercalated" structure, and each component can maintain an existence form smaller than 10nm, reducing the gap between TiO2 and SiO x The volume expansion of the particles during the charging and discharging process makes them have the characteristics of high capacity, fast charging performance and stable cycle as electrode materials. While greatly improving the energy density of lithium-ion battery negative electrode materials, they also show excellent stability and fast charging performance.
[0019] (2) The present invention synthesizes TiO2 / SiO by a two-step process of ball milling and heating in air x The bulk dual-continuous structure electrode material has a simple process and is easy to scale up, and its nano-microstructure can be controlled by changing the heating temperature and time. This work provides a solution for the structural design of the next generation of long-cycle, high-fast charging performance and high-energy density materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 The TiO2 / SiO2 described in Example 1 of the present invention x X-ray diffraction analysis XRD pattern of bulk bicontinuous structure electrode material;
[0022] Figure 2 The TiO2 / SiO2 described in Example 1 of the present invention x One of the HAADF-STEM images of the bulk bicontinuous structure electrode material;
[0023] Figure 3 The TiO2 / SiO2 described in Example 1 of the present invention x The second HAADF-STEM image of the bulk bicontinuous structure electrode material;
[0024] Figure 4 The TiO2 / SiO2 described in Example 1 of the present invention x HAADF-EDXmapping diagram of bulk bicontinuous structure electrode material;
[0025] Figure 5 The TiO2 / SiO2 described in Example 1 of the present invention xHigh-resolution transmission electron microscopy (HRSTEM) image of bulk bicontinuous structure electrode material;
[0026] Figure 6 The TiO2 / SiO2 described in Example 1 of the present invention x X-ray photoelectron spectroscopy analysis XPS diagram of Si2p orbital of bulk bicontinuous structure electrode material;
[0027] Figure 7 The TiO2 / SiO2 described in Example 1 of the present invention x Thermogravimetric images of the edge regions of bulk bicontinuous structure electrode materials;
[0028] Figure 8 The TiO2 / SiO2 described in Example 1 of the present invention x Figure 2 shows the N2 absorption and desorption of the bulk bicontinuous structure electrode material;
[0029] Fig. 9 The TiO2 / SiO2 described in Example 1 of the present invention x Structural gain diagram and synthesis mechanism diagram of bulk bicontinuous structure electrode materials;
[0030] Fig.10 The TiO2 / SiO2 described in Example 1 of the present invention x Low current density cycle diagram of lithium battery assembled with bulk bicontinuous structure electrode material (current density is 0.1A g -1 );
[0031] Fig.11 The TiO2 / SiO2 described in Example 1 of the present invention x Rate diagram of lithium battery assembled with bulk bicontinuous structure electrode material (current density is 0.1A g -1 , 0.2A g -1 , 0.5A g -1 , 1.0A g -1 , 1.5A g -1 , 2.0A g -1 , 5.0A g -1 , and finally returned to 0.1A g -1 );
[0032] Fig.12 The TiO2 / SiO2 described in Example 1 of the present invention x High current density cycle diagram of lithium battery assembled with bulk bicontinuous structure electrode material (current density is 1.0A g -1 ). DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0034] It should be noted that in the description of the embodiments of the present application, the description of the term "some specific embodiments" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0035] In this embodiment, “in the range of…” includes both end values, such as “in the range of 1 to 100” includes both end values of 1 and 100.
[0036] In the existing technology, it has become a research hotspot to improve the electrochemical performance by constructing a sophisticated nanostructure to obtain smaller volume expansion and faster ion transmission speed. However, the current TiO2 and SiO x The combination method is mostly at the micron scale or 100 nanometer scale, using the method of encapsulation and embedding. The bicontinuous structure has its unique advantages in lithium ion mass transfer and mutual stability. The TiO2 / SiO composite at a scale less than 10nm x There is no report on bi-continuous electrode materials with a capacity retention rate of more than 95% after 1000 cycles.
[0037] In order to solve the above problems, the present invention provides a TiO2 / SiO x The bulk double continuous structure electrode material comprises a first continuous structure and a second continuous structure plugged into the first continuous structure, wherein the first continuous structure is a bridged TiO2 nanoparticle, and the second continuous structure is a SiO x Nanoparticle network structure, where 0.5<x<2, SiO x The particle size of the nanoparticles is smaller than that of the TiO2 nanoparticles, and the particle size of the TiO2 nanoparticles is no greater than 10 nm.
[0038] The nanostructure designed by the present invention is a composite TiO2 / SiO x In the bulk bicontinuous structure, the bridged TiO2 nanoparticles act as both active materials and structurally stable skeletons due to their mechanical stability and low volume expansion. x , with smaller sizes in the bulk phase and continuous TiO2 nanoparticles in a bicontinuous "intercalated" structure. In this unique structure, SiO xThe network separates TiO2 into a continuous structure bridging the nanoscale, reducing the volume effect of TiO2, and its highly conductive / ion-conductive lithium product plays the role of a lithium ion transport network; at the same time, TiO2 confines SiO x The size of SiO is suppressed by the strong confinement effect. x Volume expansion and powdering due to high capacity during cycling.
[0039] Therefore, thanks to the two mutually confined domains of the bicontinuous structure, even after high-temperature sintering, TiO2 and SiO x It can still maintain a form smaller than 10nm, greatly reducing the size of TiO2 and SiO x The volume expansion of particles during the charge and discharge process. In addition, in the dual-continuous phase composite structure, the small component size will reduce the transport distance of lithium ions and accelerate the lithiation / delithiation kinetics, while the low specific surface area of the bulk phase will generate a stable solid electrolyte membrane, thereby improving its safety and electrode stability.
[0040] Preferably, the particle size of the TiO2 nanoparticles is in the range of 2 nm to 10 nm.
[0041] Furthermore, SiO x The particle size of nanoparticles ranges from 1 nm to 5 nm.
[0042] Furthermore, TiO2 / SiO x The bulk structure of the bulk bicontinuous structure electrode material is a sphere, and the diameter of the sphere is in the range of 0.1um to 5um. In the embodiment of the present invention, the sphere includes spherical structures such as elliptical and quasi-circular structures.
[0043] Based on the above solution, another embodiment of the present invention provides a TiO2 / SiO x A method for preparing a bulk bicontinuous structure electrode material comprises the following steps:
[0044] The Ti3SiC2 MAX phase ceramic powder is ball-milled, and the ball-milling conditions include: a rotation speed of 100-600 rpm and a ball-milling time of 0.5-48 h; the ball-milled product is sintered in air at a sintering temperature of 500-1200°C and a heating time of 0.5-6 h to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
[0045] Wherein, the purity of Ti3SiC2 MAX phase ceramic powder is not less than 90%.
[0046] It should be understood that Ti3SiC2 MAX phase ceramics are a new type of machinable conductive ceramic material that has attracted much attention. This type of ceramic contains more than sixty ternary carbides or nitrides, M represents the transition group front metal element, A represents the main group element, mainly the third and fourth main group elements, and X represents carbon or nitrogen. Due to the unique nano-layered crystal structure, this type of ceramic material has the properties of anti-oxidation, self-lubrication, high fracture toughness at room temperature and conductivity.
[0047] The present invention synthesizes TiO2 / SiO2 by a two-step method of ball milling and heating in air. x Bulk bicontinuous structure electrode materials, ball milling and air heating methods are mature commercial electrode material preparation methods, the process is simple and easy to scale up, and its nano-microstructure can be controlled by changing the heating temperature and time. This work provides a solution for the structural design of the next generation of long cycle, high fast charging performance and high energy density materials.
[0048] Another embodiment of the present invention provides a TiO2 / SiO x Application of bulk bicontinuous structure electrode materials as negative electrode active materials for lithium-ion batteries.
[0049] The TiO2 / SiO x Bulk phase bicontinuous structure electrode material, based on the unique advantages of nanoscale composite bicontinuous bulk phase structure, sub-10nm scale composite TiO2 / SiO x When used as lithium-ion negative electrode materials, the electrode materials with bulk bicontinuous structures exhibit excellent capacity, fast charging performance and cycle performance, and are potential application materials for high-capacity and long cycle life lithium-ion batteries.
[0050] On the basis of the above-mentioned embodiments, the present invention provides the following specific examples to further illustrate the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The experimental methods without specifying specific conditions in the following examples are usually based on the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by mass.
[0051] Example 1
[0052] This embodiment provides a TiO2 / SiO x The bulk bicontinuous structure electrode material comprises the following steps:
[0053] 1) 2 g of commercial Ti3SiC2 MAX phase ceramic powder was mixed with 24 stainless steel balls (10 balls with a diameter of 6 mm and 4 balls with a diameter of 10 mm) and ball milled at 300 rpm for 2 h;
[0054] 2) The powder obtained in step 1) was placed in a muffle furnace and sintered at 800°C for 2 h in air to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
[0055] Combination Fig. 9 As shown, the synthesis and gain mechanism of the present invention is: the intrinsic Si / Ti atomic distribution of Ti3SiC2 MAX phase ceramics is utilized, and its size is reduced by ball milling to make it easier to be oxidized, and then heated and oxidized in air. Thanks to the two mutually confined domains of the bicontinuous structure, even after high-temperature sintering, its components can still maintain an existence form of less than 10nm. This structure can greatly reduce the size of TiO2 and SiO x The volume expansion of particles during the charge and discharge process. In this sub-10 nanometer scale composite TiO2 / SiO x In the bulk bicontinuous structure, the bridged TiO2 nanoparticles (2-10 nm) serve as both active materials and structurally stable skeletons due to their mechanical stability and low volume expansion. x , with a smaller size (1-5nm) in the bulk phase and continuous TiO2 nanoparticles in a bicontinuous "intercalated" structure, which increases the capacity while stabilizing the structure, so that the volume expansion caused by the high capacity will not cause structural powdering or degradation.
[0056] The TiO2 / SiO prepared in Example 1 x Taking the bulk bicontinuous structure electrode material as an example, the morphology and structure were characterized and the results were obtained. Figure 1-8 The result graph is shown.
[0057] Figure 1 TiO2 / SiO x XRD diagram of bulk bicontinuous structure electrode material, from Figure 1 It can be seen that TiO2 / SiO x The diffraction peaks of the bulk bicontinuous structure electrode material are consistent with those of JCPDS cards No.021-071-1164 and No.01-073-224, which are anatase and rutile TiO2, respectively.
[0058] Figure 2 TiO2 / SiO x One of the HAADF-STEM images of the bulk bicontinuous structure electrode material. Figure 2 It can be seen that the bulk structure of the electrode material can be observed as an ellipsoid with a size of 200-500nm. From its surface texture, it can be seen that there are light and dark textures, which are caused by the thickness contrast of HAADF. The bright area corresponds to TiO2 and the dark area corresponds to SiO x , TiO2 and SiOx Densely distributed inside.
[0059] Figure 3 This is an enlarged HAADF-STEM image. Figure 3 It can be seen that the distribution of bright and dark areas is more obvious. The lattice fringes on the surface of the bright area are about 5nm in size, corresponding to the crystalline form of TiO2, while the dark area has no lattice fringes and the width is about 2nm, corresponding to the amorphous SiO x .
[0060] Figure 4 TiO2 / SiO x HAADF-EDX image of bulk bicontinuous structure electrode material, from Figure 4 It can be seen that the signals of Ti and Si are both continuous, which verifies that the electrode material prepared in this application is a bicontinuous structure.
[0061] Figure 5 TiO2 / SiO x HRSTEM image of bulk bicontinuous structure electrode material, from Figure 5 It can be seen that the TiO2 nanoparticles have a clear atomic phase, which verifies their bridging structure. From the FFT images corresponding to the marked areas, it can be seen that they are TiO2 with rutile and anatase crystal structures, which are bridged inside the bulk phase with a size of about 5nm. At the same time, the SiO x It is an amorphous structure, and it can be clearly seen that it is a continuous structure with a width of about 2nm, which verifies the TiO2 / SiO x Sub-10 nm bicontinuous.
[0062] Figure 6 TiO2 / SiO x XPS diagram of Si2p orbital of bulk bicontinuous structure electrode material, from Figure 6 It can be seen that the peak of Si-2p orbital can be used to judge SiO x The value of x is about 1.05.
[0063] Figure 7 TiO2 / SiO x Thermogravimetric images of the edge area of the bulk bicontinuous structure electrode material, from Figure 7 It can be seen that there is no mass loss after thermal reheating indicating that there is no or less carbon residue after heating oxidation.
[0064] Figure 8 TiO2 / SiO x Figure 1 shows the N2 absorption and desorption of bulk bicontinuous structure electrode materials. Figure 8 It can be seen that the electrode material has a low BET specific surface area (5.9 m 2g -1 ), proving its stable bulk structure.
[0065] The TiO2 / SiO prepared in Example 1 x The bulk bicontinuous structure electrode material is applied to lithium-ion batteries, and the specific steps include:
[0066] Preparation process of positive electrode sheet: using TiO2 / SiO x The bulk bicontinuous structure electrode material is used as the active material, acetylene black is used as the conductive agent, and sodium alginate is used as the binder. The mass ratio of the active material, acetylene black, and sodium alginate is 70:20:10 and dispersed in deionized water. The mixture is stirred evenly and ultrasonicated for 4 hours to obtain an electrode slurry. The electrode slurry is coated on the surface of the copper foil and dried at 85°C to obtain a positive electrode sheet. 1M LiPF is dissolved in ethylene carbonate (EC) and dimethyl carbonate (DMC) as the electrolyte, the lithium sheet is used as the negative electrode, Celgard 2400 is used as the diaphragm, and CR 2025 stainless steel is used as the battery casing to assemble into a button-type lithium-ion battery. Among them, the remaining steps of the preparation method of the lithium-ion battery are the same as the usual preparation method, which will not be elaborated here. The assembled button-type lithium-ion battery was electrochemically tested and obtained. Figure 10-12 The result graph is shown.
[0067] Fig.10 , Fig.12 These are all current density cycle diagrams of lithium batteries, such as Fig.10 As shown, at a current density of 0.1A g -1 After 580 cycles, its capacity is 671.4 mAh g -1 ;like Fig.12 As shown, when the current density is 1.0A g -1 Even after 1000 cycles, its capacity is 355.3 mAh g -1 , maintaining 95% of capacity.
[0068] Fig.11 This is the rate diagram of lithium battery. Fig.11 It can be seen that at 0.1A g -1 At this current density, its capacity is 513.5 mAh g -1 When the current density increases to 0.2A g -1 , 0.5A g -1 , 1.0A g -1 , 1.5A g -1 , 2.0A g -1 , 5.0A g -1 When the capacity is 491.1mAh g -1 ,432.1mAh g -1392.6mAh g -1 355.3mAh g -1 304.5mAh g -1 266.6mAh g -1 The results show that the sub-10nm composite TiO2 / SiO x The electrode material with bulk bicontinuous structure has the characteristics of excellent high capacity, fast charging performance and long cycle life, and is a potential application material for lithium-ion batteries.
[0069] Example 2
[0070] This embodiment provides a TiO2 / SiO x The bulk bicontinuous structure electrode material comprises the following steps:
[0071] 1) 2 g of commercial Ti3SiC2 MAX phase ceramic powder was mixed with 24 stainless steel balls (10 balls with a diameter of 6 mm and 4 balls with a diameter of 10 mm) and ball milled at 100 rpm for 3 h;
[0072] 2) The powder obtained in step 1) was placed in a muffle furnace and sintered at 600°C for 2 h in air to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
[0073] The TiO2 / SiO x As an example, the bulk bicontinuous structure electrode material was assembled into a lithium battery according to the method described in Example 1 and tested. -1 The results of constant current charge and discharge under the condition of 100V / min show that its first discharge capacity can reach 315.8 mAh g -1 , after 800 cycles, it is 264.2 mAh g -1 , the capacity retention rate reached 83.6%.
[0074] Example 3
[0075] This embodiment provides a TiO2 / SiO x The bulk bicontinuous structure electrode material comprises the following steps:
[0076] 1) 2 g of commercial Ti3SiC2 MAX phase ceramic powder was mixed with 24 stainless steel balls (10 balls with a diameter of 6 mm and 4 balls with a diameter of 10 mm) and ball milled at 500 rpm for 1 h;
[0077] 2) The powder obtained in step 1) was placed in a muffle furnace and sintered at 700°C for 4 h in air to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
[0078] The TiO2 / SiO x As an example, the bulk bicontinuous structure electrode material was assembled into a lithium battery according to the method described in Example 1 and tested. -1 The results of constant current charge and discharge under the condition of 100V / min show that its first discharge capacity can reach 368.2 mAh g -1 , after 1000 cycles, it is 266.7 mAh g -1 , the capacity retention rate reached 72.4%.
[0079] Example 4
[0080] This embodiment provides a TiO2 / SiO x The bulk bicontinuous structure electrode material comprises the following steps:
[0081] 1) 2 g of commercial Ti3SiC2 MAX phase ceramic powder was mixed with 24 stainless steel balls (10 balls with a diameter of 6 mm and 4 balls with a diameter of 10 mm) and ball milled at 150 rpm for 4 h;
[0082] 2) The powder obtained in step 1) was placed in a muffle furnace and sintered at 900°C in air for 3 h to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
[0083] The TiO2 / SiO x As an example, the bulk bicontinuous structure electrode material was assembled into a lithium battery according to the method described in Example 1 and tested. -1 The constant current charge and discharge results under the condition of 100V / min show that its first discharge capacity can reach 352.5mAh g -1 , after 200 cycles, it is 156.1 mAh g -1 , the capacity retention rate is 44.2%.
[0084] Example 5
[0085] This embodiment provides a TiO2 / SiO x The bulk bicontinuous structure electrode material comprises the following steps:
[0086] 1) 2 g of commercial Ti3SiC2 MAX phase ceramic powder was mixed with 24 stainless steel balls (10 balls with a diameter of 6 mm and 4 balls with a diameter of 10 mm) and ball milled at 500 rpm for 2 h;
[0087] 2) The powder obtained in step 1) was placed in a muffle furnace and sintered at 750°C in air for 2 h to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
[0088] The TiO2 / SiO x As an example, the bulk bicontinuous structure electrode material was assembled into a lithium battery according to the method described in Example 1 and tested. -1 The results of constant current charge and discharge under the condition of 100V / min show that its first discharge capacity can reach 274.4 mAh g -1 After 350 cycles, it is 164.2 mAh g -1 , the capacity retention rate is 59.8%.
[0089] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A TiO2 / SiO x Bulk bicontinuous structure electrode material, characterized in that: The invention comprises a first continuous structure and a second continuous structure inserted into the first continuous structure, wherein the first continuous structure is a bridged TiO2 nanoparticle, and the second continuous structure is a SiO x Nanoparticle network structure, wherein 0.5<x<2, the SiO x The particle size of the nanoparticles is smaller than that of the TiO2 nanoparticles, and the particle size of the TiO2 nanoparticles is not greater than 10 nm.
2. TiO2 / SiO according to claim 1 x Bulk bicontinuous structure electrode material, characterized in that: The particle size of the TiO2 nanoparticles is in the range of 2nm to 10nm.
3. TiO2 / SiO according to claim 2 x Bulk bicontinuous structure electrode material, characterized in that: The SiO x The particle size of nanoparticles ranges from 1 nm to 5 nm.
4. TiO2 / SiO according to claim 1 x Bulk bicontinuous structure electrode material, characterized in that: The TiO2 / SiO x The bulk structure of the bulk bicontinuous structure electrode material is a sphere, and the diameter of the sphere is in the range of 0.1um to 5um.
5. TiO2 / SiO2 as claimed in any one of claims 1 to 4 x A method for preparing a bulk bicontinuous structure electrode material, characterized in that: Includes steps: The Ti3SiC2 MAX phase ceramic powder is ball-milled, and the ball-milled product is sintered in air to obtain TiO2 / SiO x Bulk bicontinuous structure electrode materials.
6. The preparation method according to claim 5, characterized in that: The ball milling conditions include: a rotation speed of 100-600 rpm and a ball milling time of 0.5-48 h.
7. The preparation method according to claim 5, characterized in that: The sintering conditions include: sintering temperature of 500-1200° C. and heating time of 0.5-6 h.
8. The preparation method according to claim 7, characterized in that: The purity of the Ti3SiC2 MAX phase ceramic powder is not less than 90%.
9. The TiO2 / SiO2 composition according to any one of claims 1 to 4. x Application of bulk bicontinuous structure electrode materials as negative electrode active materials for lithium-ion batteries.
Citation Information
Patent Citations
Preparation of silicon dioxide / titanium dioxide composite aerogel for lithium battery negative electrode material
CN105609741A
Silicon / lithium titanium dioxide ion battery negative electrode material and preparation method thereof
CN106941172A